2021
DOI: 10.1007/s11696-021-01754-0
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and polyphenol content of different Vitis vinifera seed cultivars and two facilities of production of a functional bakery product

Abstract: This study aimed to examine the differences between the antioxidant capacity, and the total polyphenol content of the seed of eight different grape varieties. We also attempt to create a functional loaf enriched with grape seed meal. To achieve this goal, 3, 6, and 9% of the grape seed meal were added to the loaves made of bread flour and gluten-free flour mixture, and then the changes in their antioxidant and polyphenol content were examined. Based on the results, there were significant differences between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…Kapcsándi et al ( 2021) used ethanol and water in a ratio of 50:50 v/v% to extract the antioxidants and polyphenols, while methanol and water were used in a ratio of 80:20 to extract the active ingredients from the bread loaf. The results of the study showed that methanol does not provide the best extraction efficiency of these compounds [6].…”
Section: Antioxidant Properties Of Experimentally Produced Vegetarian...mentioning
confidence: 88%
See 3 more Smart Citations
“…Kapcsándi et al ( 2021) used ethanol and water in a ratio of 50:50 v/v% to extract the antioxidants and polyphenols, while methanol and water were used in a ratio of 80:20 to extract the active ingredients from the bread loaf. The results of the study showed that methanol does not provide the best extraction efficiency of these compounds [6].…”
Section: Antioxidant Properties Of Experimentally Produced Vegetarian...mentioning
confidence: 88%
“…The correlations between the total polyphenol content and measured antioxidant activities are shown in Table 3; it can be seen that a very significant (p < 0.01) positive correlation was found between the higher antioxidant activities (ABTS and FRAP) and higher total polyphenol contents in experimentally produced vegetarian sausages. The literature reports polyphenol content and antioxidant capacity depending on the grape variety [6,30,31]. In our case, the flour was obtained from the market network, and the variety was not indicated on the packaging of the grape flour.…”
Section: Antioxidant Properties Of Experimentally Produced Vegetarian...mentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, it is necessary to ensure their quality and safety. In work [4] it is shown that traditional bakery products do not differ in special useful properties, long shelf life, therefore, manufacturers are increasingly improving the formulation of their products. The solution to this problem of the quality and safety of bakery products depends not only on changes in the composition of ingredients and the balance of the nutrition structure, but also on the equipment that provides the required performance.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%